Ferromagnetism and structural deformation in monolayer alpha lead oxide induced by N and F doping: New insights from first principles. Issue 16 (4th June 2020) - Muhammady, Shibghatullah; Noor, Fatimah A.; Widita, Rena; Darma, Yudi
Abstract: We study the structural, electronic, and magnetic properties of monolayer α ‐PbO0.875 A 0.125 ( A = N, F), which are calculated using first principles. As a result, N doping induces local ferromagnetism centered at the N 2− site, originating from the spin‐down N 2p valence states. On the other hand, F doping induces nonmagnetism and induces ab ‐plane deformation, where F − receives one electron to its nearest‐neighboring Pb 1.75+ ions. N doping redshifts the bandgap of the undoped system and transforms it to be indirect, while F doping blueshifts the bandgap through the Burstein‐Moss effect. The hybridization of Pb 6p and O 2p orbitals is stronger near the A site than that of the crystal structure edge. Our result shows new insights, predicting possible experimental results for future functional device applications. Abstract : The structural, electronic, and magnetic properties of monolayer N‐ and F‐doped α ‐PbO are calculated by first principles. N doping induces local ferromagnetism centered at N 2− and decreases the bandgap of monolayer α ‐PbO. F doping induces nonmagnetism. The F − ion receives one electron to nearest‐neighboring Pb 1.75+, induces the ab ‐plane distortion, and blueshifts the bandgap through the Burstein‐Moss effect. Pb 6p‐O 2p hybridization near the doping site is stronger than that of crystal structure edge.